Computer-assisted image analysis for measuring body segmental angles during a static strength element on parallel bars: validity and reliability - Siatras, T. (Sports Biomechanics, 2011)
This study aimed to introduce a technique using computer-assisted image analysis for measuring body segmental angles during a static strength element on parallel bars. Criterion validity and intra-rater reliability of measurements were evaluated using digital photography, skin markers and a gravity-reference goniometer. Twenty male former gymnasts participated in this study. They performed a strength hold element on parallel bars (V-sit) and they were photographed with legs extended and stabilized at the highest possible level. The leg to horizontal, trunk to vertical and arm to vertical angles were calculated and examined for reliability using image-pro software. The leg angle was also examined for its validity, by simultaneously using a Myrin goniometer. The two goniometric techniques indicated high leg angle measurements agreement (R = 0.997, p < 0.001). However, Bland-Altman analysis showed that there was a slight leg angle measurement overrating using image-pro software, especially at smaller angles. The Intra-class Correlation Coefficient (ICC) values were high for leg angle (R = 0.971), trunk angle (R = 0.957) and arm angle (R = 0.945), showing an excellent test-retest agreement. It was ascertained that the measurement of segmental angles during V-sit on parallel bars using digital photography and computer-assisted image analysis can be highly reliable when taken by the same experienced examiner.